Applying "one syndrome and one product" nursing model to improve the quality of orthopedic nursing (运用"一证一品"护理模式提高骨科专科护理质量) - ZHANG Jing (张敬); TANG Ling (唐玲); ZHANG Dahua (张大华); ZHANG Xuejian (张雪键); CUI Yangfang (崔杨芳) (Association of Integrative Nursing, 2021)
In order to further improve the quality of nursing service and raise the level of nursing service, the Orthopedics and Traumatology Center of hospital has implemented the "one syndrome and one product" nursing model, carried out new explorations and practices on improving the management model of orthopedic specialist nursing quality. The program has also made specific implementations to achieve the purpose of enabling patients obtain professional and homogeneous nursing services, achieve good results in improving the level of orthopedic specialist nursing services and increase the satisfaction rate of patients in hospital. (为进一步改善专科护理服务质量, 提升护理服务水平, 医院骨伤中心推行"一证一品"护理模式, 对如何提高骨科专科护理质量管理模式进行了新的探索和实践, 并制定了具体的实施方案, 确保患者获得专业化、同质化护理服务, 提升骨科专科护理服务水平及患者住院满意度。)